The application of high pressure as an alternative to thermal processing of poultry meat - Винникова, Людмила Григорьевна; Прокопенко, Ирина Александровна (Eastern-European Journal of Enterprise Technologies, 2015)
An innovative technology that allows to get the finished product based on poultry meat by athermal processing method was considered in the paper. Research to determine the effect of high hydrostatic pressure on the total number of microorganisms in the poultry meat, as well as opportunistic pathogenic and pathogenic microflora were conducted. High-pressure processing modes, which involve the acid phosphatase enzyme inactivation, which characterizes the culinary readiness degree of poultry meat were determined. The research results of the organoleptic characteristics of samples subjected to conventional thermal processing and high hydrostatic pressure processing were presented. The changes in the product weight loss during the thermal and athermal processing of meat were shown. Based on the research results, rational modes of the high-pressure processing of poultry meat to achieve a complete culinary readiness, safety and high organoleptic characteristics of the finished product were recommended. It is proved that the application of high hydrostatic pressure is possible as an alternative to thermal processing of meat products.